Personal Branding of Fahmi Adam on Instagram in the General Election of the Gowa Regency DPRD in 2024 - Putri, Megumi Rizky; Arsyad, Armin (Malikussaleh Social and Political Reviews, 2025)
This research aims to analyse Fahmi Adam's personal branding strategy through the Instagram platform in the context of the 2024 Gowa Regency DPRD General Election campaign. The research method used is qualitative with a descriptive approach, combining Instagram content analysis, participatory observation, and in-depth interviews with Fahmi Adam, the campaign team, and active audiences. The results showed that Fahmi Adam succeeded in building an authentic, consistent, and relevant self-image with strong social, religious, and youth values. This personal branding strategy not only increased the engagement of his followers on social media, but also created emotional closeness and public trust, especially among young voters. The findings confirm the importance of using social media as a space for two-way dialogue and interaction in modern local politics, and show how a strategic digital communication approach can strengthen politicians' electability. The benefits of this research lie in providing practical insights for local politicians in designing effective and ethical digital campaigns, as well as academic contributions in the development of digital political communication studies at the local level.